2021
DOI: 10.3390/ijerph18073374
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Methods to Impute Missing Daily Ground-Level PM10 Concentrations between 2010–2017 in South Africa

Abstract: Good quality and completeness of ambient air quality monitoring data is central in supporting actions towards mitigating the impact of ambient air pollution. In South Africa, however, availability of continuous ground-level air pollution monitoring data is scarce and incomplete. To address this issue, we developed and compared different modeling approaches to impute missing daily average particulate matter (PM10) data between 2010 and 2017 using spatiotemporal predictor variables. The random forest (RF) machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…A different approach was applied in the prediction of missing PM 10 data in a different study using monitoring stations from Cape Town. It was reported that models for each site performed better in capturing the variability of PM 10 concentration [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…A different approach was applied in the prediction of missing PM 10 data in a different study using monitoring stations from Cape Town. It was reported that models for each site performed better in capturing the variability of PM 10 concentration [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…SAAQIS can be reached via their website (https://saaqis.environment.gov.za/, accessed on 22 October 2018). For our study, we selected, for each year between 2010 and 2017, all sites with more than or equal to 70% of total daily measurement data available during a year [17]. Missing data were imputed using a random forest machine learning method, including spatiotemporal predictors, like meteorological, land use and source-related variables, as described in detail in our previous paper [17].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study described the quality of ground-level PM 10 measurements in four provinces of South Africa, Gauteng, Mpumalanga, Western Cape and KwaZulu-Natal, for the years 2010-2017 [17]. The earlier study explored methods to bridge the gap in daily PM 10 data by imputing missing daily PM 10 for some sites in these provinces for the study period.…”
Section: Introductionmentioning
confidence: 99%
“…The findings were that this approach is a feasible approach to compensate for missing data. ( Arowosegbe et al., 2021 ) Health Risk Assessment of PM 2.5 and PM 2.5 -Bound Trace Elements in Thohoyandou, South Africa The study investigated the health risks of fine particulate matter grade PM 2.5 in ambient air and its trace elemental components in a rural community of South Africa. The study established that health risks exposure was high particularly for children and infants.…”
Section: Resultsmentioning
confidence: 99%